Exploring the mechanisms of organic matter degradation and methane emission during sewage sludge composting with added vesuvianite: Insights into the prediction of microbial metabolic function and enzymatic activity. (August 2019) - Jiang, Jishao; Wang, Yang; Liu, Juan; Yang, Xianli; Ren, Yuqing; Miao, Haohao; Pan, Youwei; Lv, Jinghua; Yan, Guangxuan; Ding, Linjie; Li, Yunbei
Highlights: The addition of V accelerated the OM degradation relative to control. V addition decreased the cumulative CH4 emissions by 33.6% relative to control. V decreased mcrA gene abundance and the methanogens community richness. V strengthens metabolic function and enzymatic activity related to OM degradation. Optimizing C/N and moisture content will decrease methane emission. Abstract: Effect mechanisms of organic matter (OM) degradation and methane (CH4 ) emission during sewage sludge (SS) composting with added vesuvianite (V) were studied by high-throughput sequencing (HTS) and phylogenetic investigation of communities by reconstruction of unobserved states (PICRUSt). Results show that the addition of V accelerated the OM degradation and decreased the cumulative CH4 emissions by 33.6% relative to the control. In addition, V significantly decreased the mcrA gene abundance and the methanogen community richness at the genus level. PICRUSt also indicated that V strengthens the microbial metabolic function and enzymatic activity related to OM degradation, and reduced the enzymatic activity related to CH4 production. Methanogens community variation analysis proved the ratio of carbon and nitrogen and moisture content are the significant variables affecting CH4 emissions. Thus, optimizing the ratio of carbon and nitrogen and moisture content will decrease CH4 emission during SS composting.